SUMOylating Two Distinct Sites on the A-type Potassium Channel, Kv4.2, Increases Surface Expression and Decreases Current Amplitude - Welch, Meghyn A.; Forster, Lori A.; Atlas, Selin I.; Baro, Deborah J. (Frontiers in Molecular Neuroscience, 2019)
Post-translational conjugation of Small Ubiquitin-like Modifier (SUMO) peptides to lysine (K) residues on target proteins alters their interactions. SUMOylation of a target protein can either promote its interaction with other proteins that possess SUMO binding domains, or it can prevent target protein interactions that normally occur in the absence of SUMOylation. One subclass of voltage-gated potassium channels that mediates an A-type current, IA, exists as a ternary complex comprising Kv4 pore forming subunits, Kv channel interacting proteins (KChIP) and transmembrane dipeptidyl peptidase like proteins (DPPL). SUMOylation could potentially regulate intra- and/or intermolecular interactions within the complex. This study began to test this hypothesis and showed that Kv4.2 channels were SUMOylated in the rat brain and in human embryonic kidney (HEK) cells expressing a GFP-tagged mouse Kv4.2 channel (Kv4.2g). Prediction software identified two putative SUMOylation sites in the Kv4.2 C-terminus at K437 and K579. These sites were conserved across mouse, rat, and human Kv4.2 channels and across mouse Kv4 isoforms. Increasing Kv4.2g SUMOylation at each site by 30% produced a significant 22-50% decrease in IA Gmax, and a 70-95% increase in channel surface expression. Site-directed mutagenesis of Kv4.2g showed that K437 SUMOylation regulated channel surface expression, while K579 SUMOylation controlled IA Gmax. The K579R mutation mimicked and occluded the SUMOylation-mediated decrease in IA Gmax, suggesting that SUMOylation at K579 blocked an intra- or inter-protein interaction involving K579. The K437R mutation did not obviously alter channel surface expression or biophysical properties, but it did block the SUMOylation-mediated increase in channel surface expression. Interestingly, enhancing K437 SUMOylation in the K579R mutant roughly doubled channel surface expression, but produced no change in IA Gmax, suggesting that the newly inserted channels were electrically silent. This is the first report that Kv4.2 channels are SUMOylated and that SUMOylation can independently regulate Kv4.2 surface expression and IA Gmax in opposing directions. The next step will be to determine if/how SUMOylation affects Kv4 interactions within the ternary complex.